Effects of water exchange protocols on water quality, sedimentation rate and production performance of Penaeus monodon in earthen ponds - Mohanty, R.K.; Mishra, Atmaram; Panda, D.K.; Patil, D.U. (Hindawi Limited, 2015)
This study was carried out in farmers’ fields to quantify the total water and consumptive water use in grow-out culture of Penaeus monodon under recommended package of practice with two different water management protocols: T1, with no water exchange and T2, with regulated water exchange. Treatment-wise estimated total water use, was 2.09 and 2.43 ha-m 122 day 1, while the computed consumptive water use index (m3 kg 1 biomass) was 5.35 and 6.02 in T1 and T2 respectively. Lower rates of water exchange (T2) showed significantly improved (P < 0.05) crop performance in terms of performance index (19.75 0.75), production-size index (74.1 3.4), survival rate (80.13 1.7%) and productivity (2.44 0.08 t) over the zero water exchange. The shrimp pond water quality suitability index (WQSI) infers that regulated water exchange (T2) improved the overall suitability of water quality for shrimp culture. WQSI up to 90 days of culture ranged between 7.5–9.0 in T2, needs little management while in the last month of rearing, it was good with moderate management requirements. Treatment-wise sediment load ranged between 50.4–56.3 m3 t1 shrimp biomass. High intensity of water exchange and low apparent feed conversion ratio influenced in lowering the sedimentation rate. Regulated water exchange protocol (T2) performed well (higher net total water productivity and net consumptive water productivity) against no water exchange (T1). A higher OV:CC ratio (ratio of the output value to the cost of cultivation) indicated that T2 had a distinct edge over the T1 protocol.